2010
DOI: 10.1007/s11307-010-0433-7
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Assessment of Diffusion-Weighted MR Imaging in Patients with Primary Rectal Cancer: Correlation with FDG-PET/CT

Abstract: PurposeThe aim of the study was to assess correlations between parameters on diffusion-weighted imaging and 2-deoxy-2-[18F]fluoro-d-glucose–positron emission tomography/computed tomography (FDG-PET/CT) in rectal cancer.ProceduresThirty-three consecutive patients with pathologically confirmed rectal adenocarcinoma were included in this study. Apparent diffusion coefficient (ADC) maps were generated to calculate ADCmean (average ADC), ADCmin (lowest ADC), tumor volume, and total diffusivity index (TDI). PET/CT e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

12
58
0
2

Year Published

2012
2012
2013
2013

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 76 publications
(72 citation statements)
references
References 38 publications
12
58
0
2
Order By: Relevance
“…Ho et al (17) found no significant correlation between ADC min and SUV max in patients with primary cervical tumor. In that study, however, a significantly inverse correlation between the relative ADC min (defined as ADC min / ADC mean ratio) and relative SUV max was observed in patients with adeno- The authors concluded that the significant negative correlation between ADC and SUV suggests an association between tumor cellularity and metabolic activity in primary rectal adenocarcinoma (18). Neoadjuvant chemoradiotherapy has become a standard treatment for locally advanced rectal cancer.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Ho et al (17) found no significant correlation between ADC min and SUV max in patients with primary cervical tumor. In that study, however, a significantly inverse correlation between the relative ADC min (defined as ADC min / ADC mean ratio) and relative SUV max was observed in patients with adeno- The authors concluded that the significant negative correlation between ADC and SUV suggests an association between tumor cellularity and metabolic activity in primary rectal adenocarcinoma (18). Neoadjuvant chemoradiotherapy has become a standard treatment for locally advanced rectal cancer.…”
Section: Discussionmentioning
confidence: 88%
“…To our knowledge, few studies have evaluated the relationship between ADC and SUV in cancer patients (16)(17)(18). The aim of the present study was to retrospectively assess the correlation between the minimum ADC (ADC min ) on DWI and maximum SUV (SUV max ) values from FDG PET-CT in rectal cancer.…”
mentioning
confidence: 99%
“…A novel functional parameter-termed total lesion glycolysis (TLG) and defined as the standardized uptake value (SUV) multiplied by metabolic tumor volume (MTV)-has been described previously (17). TLG integrates both anatomic and biologic data and has been shown to predict prognosis in breast, colorectal, and lung cancers (18)(19)(20)(21)(22). However, the prognostic value of TLG in patients with NPC has not been sufficiently evaluated.…”
mentioning
confidence: 99%
“…Because DW-MRI is completely non-invasive, does not require ionizing radiation or injection of contrast material, and does not cause patient discomfort, it is a potentially powerful tool in the detection of rectosigmoid cancer. In addition, this technique can be easily added to an MR examination protocol because it requires only a minimal prolongation of the examination time (20)(21)(22)(23). It would be a useful adjunct to conventional sequences.…”
Section: Discussionmentioning
confidence: 99%